Enriching Work-integrated Learning: Conceptions of Integrating Indigenous Reflective Practices - Lucas, P; Hains-Wesson, R (Informa UK Limited, 2025)
In an increasingly multicultural and globally connected world, educators are called to critically reflect on how their own cultural lenses shape approaches to student learning, particularly in Work-Integrated Learning (WIL). This conceptual paper explores how reflective practice in WIL can be deepened by engaging with diverse ways of knowing, such as First Nations perspectives. While Western models of reflection remain dominant, they may not fully capture the lived experiences or worldviews of all learners. By identifying the limitations of conventional reflective frameworks and engaging with alternative epistemologies through literature and informal discussions with Indigenous curriculum experts, the authors propose a more inclusive lens for understanding reflection in WIL. These reflective dialogues helped shape a model encouraging more culturally responsive and meaningful student engagement with work focused learning. The paper concludes with practical recommendations for educators seeking to respectfully integrate Indigenous ways of knowing into WIL pedagogy, contributing to more holistic and equitable learning experiences.
Keywords: 3901 Curriculum and Pedagogy; 3903 Education Systems; 3904 Specialist Studies In Education; 39 Education; Generic health relevance; 13 Education; 39 Education; Reflective practice; work-integrated learning; Indigenous understandings; philosophy; cultural context